Analiza predtekmovalnega stanja in vedenja - Tušak, Matej (Psihološka obzorja (Ljubljana), 1995)
When we talk about athlete's pre-competition states, we think about different behaviour characteristics including emotional states on the day before the competition. Athlete's problems with copying stress and anxieties make them searching for psychological help (in psychological preparation). The basic assumption of any interventions for improving emotional states is good analysing of athlete's pre-competition state and behaviour. We have some instruments to measure it today. An instrument by B. Rushall (pre-competition state questionnaire) was applied on 156 athlete's, both male and female. Differences between male and female were found, also between individual and group sports. A latent structure of an instrument was investigated. Four factors of pre-competition state and behaviour were found. Results will help to structure preventive interventions for improving athlete's pre-competition situation.
Keywords: športniki; psihologija; psychology; tekmovanje; anksioznost; duševno stanje; stres; vedenje; psihična priprava